A fuel cell catalytic material and preparation method thereof
By preparing fuel cell catalytic materials containing two-dimensional metal organic framework structures, the problems of large mass transfer resistance and low utilization of active sites caused by Nafion overcoating the catalyst are solved, and the full play of catalyst activity and fuel cell performance are achieved. promote.
Patent Information
- Application Number
- CN202310175379.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-02-28
AI Technical Summary
The existing Nafion will overcoat the catalyst, resulting in large local oxygen mass transfer resistance and low utilization of catalyst active sites, which will not fully exert the activity of the catalyst, thereby limiting the performance improvement of fuel cells.
By adopting a method of preparing a fuel cell catalytic material, by mixing a metal salt, an organic ligand, an active agent and a reaction solvent, filtering, washing and drying after the reaction, and then dispersing it in the first organic solvent and the second organic solvent, Reflux and stirring are carried out, then dispersed in an oxidant, and finally dispersed in a Nafion solution. After ball milling and sonication, a catalytic material containing a two-dimensional metal organic framework structure is prepared.
It effectively reduces the local oxygen mass transfer resistance on the catalyst surface, improves the utilization rate of active sites, promotes the rapid transmission of cathode oxygen, optimizes the three-phase gas-solid-liquid interface on the catalyst surface, and is conducive to the low-platinum content proton exchange membrane fuel system development.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cells, and in particular to a fuel cell catalytic material and a preparation method thereof. Background Art
[0002] Compared with traditional energy conversion technologies such as internal combustion engines, fuel cells are highly efficient energy conversion devices that convert chemical energy in fuel into electrical energy. The reaction process is not limited by the Carnot cycle and has higher energy conversion efficiency and lower greenhouse gas emissions. Among many fuel cells, proton exchange membrane fuel cells have attracted much attention due to their cleanliness, high efficiency, zero pollution, low operating temperature, and rapid startup. As a key component of proton exchange membrane fuel cells, proton exchange membrane (PEM) is mainly responsible for transmitting protons and blocking fuel penetration. Its performance directly determines the service life and efficiency of the fuel cell.
[0003] Generally, the catalyst layer in a proton exchange membrane fuel cell is composed of a catalyst and an ionomer, which is the main place where electrochemistry occurs and the core component of the membrane electrode. Among them, the ionomer can provide a channel for protons and reaction gases to reach the catalyst, transport water molecules generated at the cathode, and at the same time, act as a binder.
[0004] At present, the widely used catalyst layer ionomer is chain perfluorosulfonic acid resin (Nafion), which can achieve rapid proton conduction. However, Nafion will over-coat the catalyst, resulting in greater local oxygen mass transfer resistance and lower catalyst active site utilization, which cannot fully exert the activity of the catalyst, making it difficult to improve the performance of the fuel cell. Summary of the invention
[0005] Based on this, an embodiment of the present invention provides a fuel cell catalytic material and a preparation method thereof, aiming to solve the problems that the existing Nafion will over-coat the catalyst, causing greater local oxygen mass transfer resistance and lower catalyst active site utilization, and failing to fully exert the activity of the catalyst.
[0006] To achieve the above objectives, on the one hand, an embodiment of the present invention provides a method for preparing a fuel cell catalytic material, comprising the following steps:
[0007] S01, mixing the metal salt, the organic ligand, the active agent and the reaction solvent in a molar ratio of 1: (0.5-8): (0.5-4): (50-800) to obtain a mixed solution; reacting the mixed solution at 60° C. to 300° C. for 8 h to 96 h to obtain a powdered solid; filtering the powdered solid, washing, and drying to obtain a powder;
[0008] S02, dispersing the powder in step S01 in a first organic solvent, adding a second organic solvent, stirring evenly to obtain a mixture; reflux the mixture at 60° C. to 200° C. for 4 h to 24 h to obtain a powder containing sulfur functionalization; dispersing the sulfur functionalized powder in an oxidant, stirring for 12 h to 96 h, centrifuging, and drying to obtain a solid powder;
[0009] S03, dispersing the solid powder of step S02 in Nafion solution to obtain a mixture solution; uniformly mixing the mixture solution, catalyst, third organic solvent and H2O to obtain a slurry; ball-milling the slurry, stirring it, and then ultrasonicating it to obtain a fuel cell catalytic material.
[0010] As a preferred embodiment, in step S01,
[0011] The molar ratio of the metal salt to the organic ligand is preferably 1:(1-3); the molar ratio of the metal salt to the activator is 1:(1-3); the molar ratio of the metal salt to the reaction solvent is preferably 1:(100-400).
[0012] The metal salt is Al(NO3)3·9H2O, Cr(NO3)3·9H2O, Zn(NO3)2·9H2O or Zn(NO3)2·6H2O.
[0013] The organic ligand is 2-aminoterephthalic acid, 5-aminophthalic acid, m-phenylenediamine or o-phenylenediamine.
[0014] The active agent is one or a mixture of at least two of cetyltrimethylammonium bromide, tetramethylammonium hydroxide, disodium lauryl sulfosuccinate, disodium fatty alcohol polyoxyethylene ether (3) sulfosuccinate and sucrose ester.
[0015] The reaction solvent is methanol, ethanol, ethylene glycol, propanol, propylene glycol, butanol, H2O, N,N-dimethylformamide or N,N-dimethylacetamide.
[0016] The mixing is carried out by stirring and ultrasonic mixing at 20°C to 40°C, preferably at 25°C to 30°C.
[0017] The reaction temperature is preferably 80°C to 150°C.
[0018] The washing is performed by washing with a solvent for 3 to 5 times, preferably 3 times.
[0019] The drying is carried out at 20° C. to 100° C., preferably at 60° C. to 100° C. The drying is preferably carried out in an oven.
[0020] As a preferred embodiment, in step S02,
[0021] The mass ratio of the powder to the first organic solvent is 1:(10-300), preferably 1:(20-40); the mass ratio of the powder to the second organic solvent is 1:(1-10), preferably 1:(2-7); the mass ratio of the sulfur-functionalized powder to the oxidant is 1:(50-400), preferably 1:(50-100).
[0022] The first organic solvent is preferably toluene, methanol, ethanol, n-propanol, isopropanol, n-butanol or n-hexane.
[0023] The second organic solvent is preferably 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 11-mercaptoundecyltrimethoxysilane or silane-polyethylene glycol-mercapto.
[0024] The oxidant is preferably H2O2, KMnO4, HNO3, concentrated sulfuric acid, trivalent cobalt salt or potassium dichromate.
[0025] The reflux is preferably performed at 60° C. to 100° C. for 4 h to 12 h.
[0026] The stirring time is preferably 12 h to 24 h.
[0027] The drying temperature is 30°C to 100°C, preferably 60°C to 80°C.
[0028] As a preferred implementation, in step S03,
[0029] The mass ratio of the solid powder to the Nafion solution is 1:(1-18), preferably 1:(4-8).
[0030] The dispersion is achieved by stirring for 12 h to 96 h, preferably by stirring for 12 h to 24 h.
[0031] The mass ratio of the third organic solvent to the H2O is (2-5):1, preferably (2-4):1.
[0032] The solid content of the catalyst is 2% to 10%, preferably 7% to 10%; the I / C ratio of the catalyst is 0.5 to 1, preferably 0.7:1.
[0033] The catalyst is a Pt / C catalyst.
[0034] The third organic solvent is preferably one or a mixture of at least two of n-propanol, isopropanol, methanol, ethanol and propanol.
[0035] The ball milling time is 12 h to 96 h, preferably 24 h to 72 h.
[0036] The stirring time is 1 h to 12 h, preferably 1 h to 5 h.
[0037] The ultrasonic time is 0.3h to 4h, preferably 0.5h to 2h.
[0038] On the other hand, an embodiment of the present invention also provides a fuel cell catalyst material prepared by the above preparation method.
[0039] The fuel cell catalytic material contains a two-dimensional metal organic framework structure.
[0040] The present application can effectively solve the problems that the existing Nafion will over-coat the catalyst, resulting in a large local oxygen mass transfer resistance and a low utilization rate of the catalyst active sites, and the catalyst activity cannot be fully exerted. The fuel cell catalytic material prepared in the present application contains a two-dimensional metal organic framework structure, which can effectively reduce the local oxygen mass transfer resistance on the catalyst surface, improve the utilization rate of the active sites, and facilitate the faster transmission of cathode oxygen to the catalyst surface; and can effectively optimize the gas-solid-liquid three-phase interface on the catalyst surface, which is conducive to the development of low-platinum content proton exchange membrane fuel systems. The preparation method of the present application is simple, the preparation cost is low, the preparation time is short, the production efficiency is high, and it is easy to batch or large-scale production.
[0041] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, top, bottom...), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture. If the specific posture changes, the directional indication will also change accordingly.
[0044] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0045] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it may be directly on the other element or there may be an intermediate element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be an intermediate element at the same time.
[0046] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or suggesting their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0047] At present, Nafion will over-coat the catalyst, resulting in greater local oxygen mass transfer resistance and lower catalyst active site utilization, which makes it impossible to fully exert the activity of the catalyst, thus making it difficult to improve the performance of the fuel cell. Based on this, it is necessary to provide a fuel cell catalytic material and a preparation method thereof to solve the above technical problems.
[0048] To achieve the above objectives, on the one hand, an embodiment of the present invention provides a method for preparing a fuel cell catalytic material, comprising the following steps:
[0049] S01. Mix the metal salt, organic ligand, active agent and reaction solvent in a molar ratio of 1: (0.5-8): (0.5-4): (50-800) (for example, 1: 0.5: 0.5: 50, 1: 3: 2: 200, 1: 8: 4: 800, etc.) to obtain a mixed solution; react the mixed solution at 60° C. to 300° C. (which may be 60° C., 200° C., or 300° C., etc.) for 8 h to 96 h (which may be 8 h, 36 h, or 96 h, etc.) to obtain a powdered solid; filter, wash and dry the powdered solid to obtain a powder;
[0050] S02, dispersing the powder in step S01 in a first organic solvent, adding a second organic solvent, stirring evenly to obtain a mixture; reflux the mixture at 60° C. to 200° C. (can be 60° C., 100° C., or 200° C., etc.) for 4 h to 24 h (can be 4 h, 12 h, or 24 h, etc.) to obtain a powder containing sulfur functionalization; dispersing the sulfur functionalized powder in an oxidant, stirring for 12 h to 96 h (can be 12 h, 58 h, or 96 h, etc.), centrifuging, and drying to obtain a solid powder;
[0051] S03, dispersing the solid powder of step S02 in Nafion solution to obtain a mixture solution; uniformly mixing the mixture solution, catalyst, third organic solvent and H2O to obtain a slurry; ball-milling the slurry, stirring it, and then ultrasonicating it to obtain a fuel cell catalytic material.
[0052] As a preferred embodiment, in step S01,
[0053] The molar ratio of the metal salt to the organic ligand is preferably 1:(1-3), for example, 1:1, 1:2, 1:3, etc.; the molar ratio of the metal salt to the active agent is 1:(1-3), for example, 1:1, 1:2, 1:3, etc.; the molar ratio of the metal salt to the reaction solvent is preferably 1:(100-400), for example, 1:100, 1:250, 1:400, etc.
[0054] The metal salt is Al(NO3)3·9H2O, Cr(NO3)3·9H2O, Zn(NO3)2·9H2O or Zn(NO3)2·6H2O.
[0055] The organic ligand is 2-aminoterephthalic acid, 5-aminophthalic acid, m-phenylenediamine or o-phenylenediamine.
[0056] The active agent is one or a mixture of at least two of cetyltrimethylammonium bromide, tetramethylammonium hydroxide, disodium lauryl sulfosuccinate, disodium fatty alcohol polyoxyethylene ether (3) sulfosuccinate and sucrose ester.
[0057] The reaction solvent is methanol, ethanol, ethylene glycol, propanol, propylene glycol, butanol, H2O, N,N-dimethylformamide or N,N-dimethylacetamide.
[0058] The mixing is performed by stirring and ultrasonic mixing at 20°C to 40°C (may be 20°C, 30°C, or 40°C, etc.), preferably at 25°C to 30°C.
[0059] The reaction temperature is preferably 80°C to 150°C.
[0060] The washing is performed with a solvent (deionized water) for 3 to 5 times, preferably 3 times.
[0061] The drying is performed at 20° C. to 100° C. (may be 20° C., 60° C., or 100° C., etc.), preferably at 60° C. to 100° C. The drying is preferably performed in an oven.
[0062] As a preferred embodiment, in step S02,
[0063] The mass ratio of the powder to the first organic solvent is 1:(10-300), preferably 1:(20-40), for example, 1:10, 1:200, 1:300, etc.; the mass ratio of the powder to the second organic solvent is 1:(1-10), preferably 1:(2-7), for example, 1:1, 1:7, 1:10, etc.; the mass ratio of the sulfhydryl-functionalized powder to the oxidant is 1:(50-400), preferably 1:(50-100), for example, 1:50, 1:200, 1:400, etc.
[0064] The first organic solvent is preferably toluene, methanol, ethanol, n-propanol, isopropanol, n-butanol or n-hexane.
[0065] The second organic solvent is preferably 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 11-mercaptoundecyltrimethoxysilane or silane-polyethylene glycol-mercapto.
[0066] The oxidant is preferably H2O2, KMnO4, HNO3, concentrated sulfuric acid, trivalent cobalt salt or potassium dichromate.
[0067] The reflux is preferably performed at 60° C. to 100° C. for 4 h to 12 h.
[0068] The stirring time is preferably 12 h to 24 h.
[0069] The drying temperature is 30°C to 100°C (can be 30°C, 60°C, or 100°C, etc.), preferably 60°C to 80°C.
[0070] As a preferred implementation, in step S03,
[0071] The mass ratio of the solid powder to the Nafion solution is 1:(1-18), preferably 1:(4-8), for example, 1:1, 1:8, 1:18, etc.
[0072] The dispersion is achieved by stirring for 12 h to 96 h, preferably by stirring for 12 h to 24 h.
[0073] The mass ratio of the third organic solvent to the H2O is (2-5):1, preferably (2-4):1, for example, 2:1, 3:1, 5:1, etc.
[0074] The solid content of the catalyst is 2% to 10%, preferably 7% to 10%; the I / C ratio of the catalyst is 0.5 to 1, preferably 0.7:1.
[0075] The catalyst is a Pt / C catalyst.
[0076] The third organic solvent is preferably one or a mixture of at least two of n-propanol, isopropanol, methanol, ethanol and propanol.
[0077] The ball milling time is 12 h to 96 h, preferably 24 h to 72 h, for example, 12 h, 69 h, or 96 h.
[0078] The stirring time is 1 h to 12 h, preferably 1 h to 5 h, for example, 1 h, 6 h, or 12 h.
[0079] The ultrasonic time is 0.3h to 4h, preferably 0.5h to 2h. For example, it can be 0.3h, 2h, or 4h.
[0080] On the other hand, an embodiment of the present invention also provides a fuel cell catalyst material prepared by the above preparation method.
[0081] The fuel cell catalytic material contains a two-dimensional metal organic framework structure.
[0082] The present application can effectively solve the problems that the existing Nafion will over-coat the catalyst, resulting in a large local oxygen mass transfer resistance and a low utilization rate of the catalyst active sites, and the catalyst activity cannot be fully exerted. The fuel cell catalytic material prepared in the present application contains a two-dimensional metal organic framework structure, which can effectively reduce the local oxygen mass transfer resistance on the catalyst surface, improve the utilization rate of the active sites, and facilitate the faster transmission of cathode oxygen to the catalyst surface; and can effectively optimize the gas-solid-liquid three-phase interface on the catalyst surface, which is conducive to the development of low-platinum content proton exchange membrane fuel systems. The preparation method of the present application is simple, the preparation cost is low, the preparation time is short, the production efficiency is high, and it is easy to batch or large-scale production.
[0083] Example 1
[0084] A method for preparing a fuel cell catalytic material comprises the following steps:
[0085] S01, 0.84g of metal salt, 0.29g of organic ligand, an active agent (0.40g of hexadecyltrimethylammonium bromide + 2ml of tetramethylammonium hydroxide) and 15ml of reaction solvent are mixed uniformly to obtain a mixed solution; the mixed solution is reacted at 100°C (generally, the mixed solution is placed in a polytetrafluoroethylene reactor, and the reactor is then tightened and placed in an oven for reaction) for 17h to obtain a powdery solid (NH2-MIL-53(Al) solid); the powdery solid is filtered, washed, and dried to obtain a powder (NH2-MIL-53(Al) powder);
[0086] S02, dispersing 1.0 g of the powder in step S01 in 100 ml of a first organic solvent, adding 3.5 ml of a second organic solvent, stirring evenly to obtain a mixture; reflux the mixture at 80° C. for 4 h to obtain a powder containing sulfur functionalization (MIL-53(Al)-SH); dispersing 500 mg of the sulfur functionalized powder in 30 ml of an oxidant, stirring for 12 h, centrifuging, and drying to obtain a solid powder (MIL-53(Al)-SO3H powder);
[0087] S03. Disperse 200 mg of the solid powder of step S02 in 4 g of Nafion solution to obtain a mixture solution; mix 0.92 g of the mixture solution, 0.4 g of the catalyst, a third organic solvent (2.4117 g of n-propanol and 2.4117 g of isopropanol) and 0.9647 g of H2O to obtain a slurry; ball-mill the slurry, stir it, and then ultrasonicate it to obtain a fuel cell catalytic material.
[0088] In step S01,
[0089] The metal salt is Al(NO3)3·9H2O.
[0090] The organic ligand is 2-aminoterephthalic acid.
[0091] The active agent is a mixture of hexadecyltrimethylammonium bromide and tetramethylammonium hydroxide.
[0092] The reaction solvent is H2O.
[0093] The mixing is carried out by stirring and ultrasonic mixing at 25°C.
[0094] The washing is performed by washing with deionized water for 3 times.
[0095] The drying is performed at 80° C. for 16 hours in an oven.
[0096] In step S02,
[0097] The first organic solvent is toluene.
[0098] The second organic solvent is 3-mercaptopropyltrimethoxysilane.
[0099] The oxidant is H2O2 and the drying temperature is 80°C.
[0100] In step S03,
[0101] The dispersion was achieved by stirring for 24 h.
[0102] The solid content of the catalyst is 2% to 10%; the I / C ratio of the catalyst is 0.5 to 1.
[0103] The catalyst is a Pt / C catalyst.
[0104] The third organic solvent is a mixture of n-propanol and isopropanol.
[0105] The ball milling time was 72 hours, the stirring time was 1 hour, and the ultrasonic time was 0.3 hours.
[0106] The prepared fuel cell catalyst material was made into a membrane electrode and its performance was tested. The oxygen permeability of Pt / C@NH2-MIL-53(Al) / Nafion was 31 Barrer and the local oxygen mass transfer resistance was 37.5 s·m -1 The power density of Pt / C@NH2-MIL-53(Al) / Nafion is 1.05 W·cm -1 .
[0107] Example 2
[0108] A method for preparing a fuel cell catalytic material comprises the following steps:
[0109] S01, 0.84g of metal salt, 0.28g of organic ligand, an active agent (0.40g of hexadecyltrimethylammonium bromide + 2ml of tetramethylammonium hydroxide) and 13ml of reaction solvent are mixed evenly to obtain a mixed solution; the mixed solution is reacted at 100°C (generally, the mixed solution is placed in a polytetrafluoroethylene reactor, and the reactor is then tightened and placed in an oven for reaction) for 17h to obtain a powdery solid (NH2-CAU-10(Al)); the powdery solid is filtered, washed, and dried to obtain a powder (NH2-CAU-10(Al) powder);
[0110] S02, dispersing 1.0 g of the powder in step S01 in 100 ml of the first organic solvent, adding 3.5 ml of the second organic solvent, stirring evenly to obtain a mixture; reflux the mixture at 80° C. for 4 h to obtain a powder containing sulfur functionalization (CAU-10(Al)-SH); dispersing 500 mg of the sulfur functionalized powder in 30 ml of an oxidant, stirring for 12 h, centrifuging, and drying to obtain a solid powder (CAU-10(Al)-SO3H powder);
[0111] S03. Disperse 200 mg of the solid powder of step S02 in 4 g of Nafion solution to obtain a mixture solution; mix 0.92 g of the mixture solution, 0.4 g of the catalyst, a third organic solvent (2.4117 g of n-propanol and 2.4117 g of isopropanol) and 0.9647 g of H2O to obtain a slurry; ball-mill the slurry, stir it, and then ultrasonicate it to obtain a fuel cell catalytic material.
[0112] In step S01,
[0113] The metal salt is Al(NO3)3·9H2O.
[0114] The organic ligand is 5-aminophthalic acid.
[0115] The active agent is a mixture of hexadecyltrimethylammonium bromide and tetramethylammonium hydroxide.
[0116] The reaction solvent is H2O.
[0117] The mixing is carried out by stirring and ultrasonic mixing at 25°C.
[0118] The washing is performed by washing with deionized water for 3 times.
[0119] The drying is performed at 80° C. for 16 hours in an oven.
[0120] In step S02,
[0121] The first organic solvent is toluene.
[0122] The second organic solvent is 3-mercaptopropyltrimethoxysilane.
[0123] The oxidant is H2O2 and the drying temperature is 80°C.
[0124] In step S03,
[0125] The dispersion was achieved by stirring for 24 h.
[0126] The solid content of the catalyst is 2% to 10%; the I / C ratio of the catalyst is 0.5 to 1.
[0127] The catalyst is a Pt / C catalyst.
[0128] The third organic solvent is a mixture of n-propanol and isopropanol.
[0129] The ball milling time was 72 hours, the stirring time was 1 hour, and the ultrasonic time was 0.3 hours.
[0130] The prepared fuel cell catalyst material was made into a membrane electrode for performance testing. The oxygen permeability of Pt / C@NH2-CAU-10(Al) / Nafion was 26 Barrer, the local oxygen mass transfer resistance was 41.5 s·m-1, and the power density of Pt / C@NH2-CAU-10(Al) / Nafion was 0.96 W·cm -1 .
[0131] Example 3
[0132] A method for preparing a fuel cell catalytic material comprises the following steps:
[0133] S01, 0.84g of metal salt, 0.29g of organic ligand, an active agent (0.40g of hexadecyltrimethylammonium bromide + 2ml of tetramethylammonium hydroxide) and 15ml of reaction solvent are mixed uniformly to obtain a mixed solution; the mixed solution is reacted at 100°C (generally, the mixed solution is placed in a polytetrafluoroethylene reactor, and the reactor is then tightened and placed in an oven for reaction) for 17h to obtain a powdery solid (NH2-MIL-53(Al) solid); the powdery solid is filtered, washed, and dried to obtain a powder (NH2-MIL-53(Al) powder);
[0134] S02, dispersing 1.0 g of the powder in step S01 in 100 ml of a first organic solvent, adding 3.5 ml of a second organic solvent, stirring evenly to obtain a mixture; reflux the mixture at 80° C. for 4 h to obtain a powder containing sulfur functionalization (MIL-53(Al)-SH); dispersing 500 mg of the sulfur functionalized powder in 30 ml of an oxidant, stirring for 12 h, centrifuging, and drying to obtain a solid powder (MIL-53(Al)-SO3H powder);
[0135] S03. Disperse 100 mg of the solid powder of step S02 in 4.5 g of Nafion solution to obtain a mixture solution; mix 0.92 g of the mixture solution, 0.4 g of the catalyst, a third organic solvent (2.4117 g of n-propanol and 2.4117 g of isopropanol) and 0.9647 g of H2O to obtain a slurry; ball-mill the slurry, stir it, and then ultrasonicate it to obtain a fuel cell catalytic material.
[0136] In step S01,
[0137] The metal salt is Al(NO3)3·9H2O.
[0138] The organic ligand is 2-aminoterephthalic acid.
[0139] The active agent is a mixture of hexadecyltrimethylammonium bromide and tetramethylammonium hydroxide.
[0140] The reaction solvent is H2O.
[0141] The mixing is carried out by stirring and ultrasonic mixing at 25°C.
[0142] The washing is performed by washing with deionized water for 3 times.
[0143] The drying is performed at 80° C. for 16 hours in an oven.
[0144] In step S02,
[0145] The first organic solvent is toluene.
[0146] The second organic solvent is 3-mercaptopropyltrimethoxysilane.
[0147] The oxidant is H2O2 and the drying temperature is 80°C.
[0148] In step S03,
[0149] The dispersion was achieved by stirring for 24 h.
[0150] The solid content of the catalyst is 2% to 10%; the I / C ratio of the catalyst is 0.5 to 1.
[0151] The catalyst is a Pt / C catalyst.
[0152] The third organic solvent is a mixture of n-propanol and isopropanol.
[0153] The ball milling time was 72 hours, the stirring time was 1 hour, and the ultrasonic time was 0.3 hours.
[0154] The prepared fuel cell catalyst material was made into a membrane electrode for performance testing. The oxygen permeability of Pt / C@NH2-MIL-53 / Nafion was 28 Barrer, and the local oxygen mass transfer resistance was 42.3 s·m -1 The power density of Pt / C@NH2-MIL-53 / Nafion is 0.94 W·cm -1 .
[0155] Comparative Example 1
[0156] A method for preparing a fuel cell catalytic material comprises the following steps:
[0157] 0.92 g of Nafion solution, 0.4 g of catalyst, an organic solvent (2.4117 g of n-propanol and 2.4117 g of isopropanol) and 0.9647 g of H2O were mixed uniformly to obtain slurry; the slurry was ball-milled, stirred, and then ultrasonicated to obtain a fuel cell catalytic material.
[0158] The dispersion was achieved by stirring for 24 h.
[0159] The solid content of the catalyst is 2% to 10%; the I / C ratio of the catalyst is 0.5 to 1.
[0160] The catalyst is a Pt / C catalyst.
[0161] The organic solvent is a mixture of n-propanol and isopropanol.
[0162] The ball milling time was 72 hours, the stirring time was 1 hour, and the ultrasonic time was 0.3 hours.
[0163] The prepared fuel cell catalyst material was made into a membrane electrode for performance testing. The oxygen permeability of Nafion is 3 Barrer, and the local oxygen mass transfer resistance of Pt / C@Nafion is 54.8 s·m -1 , the power density of Pt / C@Nafion is 0.85W·cm -1 .
[0164] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a fuel cell catalyst material, characterized in that: The steps include: S01. Mix the metal salt, organic ligand, active agent and reaction solvent in a molar ratio of 1: (0.5-8): (0.5-4): (50-800) to obtain a mixed solution; react the mixed solution at 60° C. to 300° C. for 8 h to 96 h to obtain a powdered solid; filter, wash and dry the powdered solid to obtain a powder; S02, dispersing the powder in step S01 in a first organic solvent, adding a second organic solvent, stirring evenly to obtain a mixture; reflux the mixture at 60° C. to 200° C. for 4 h to 24 h to obtain a powder containing sulfur functionalization; dispersing the sulfur functionalized powder in an oxidant, stirring for 12 h to 96 h, centrifuging, and drying to obtain a solid powder; S03, dispersing the solid powder of step S02 in a Nafion solution to obtain a mixture solution; uniformly mixing the mixture solution, the catalyst, the third organic solvent and H2O to obtain a slurry; ball-milling the slurry, stirring it, and then ultrasonicating it to obtain a fuel cell catalytic material; In step S02, the first organic solvent is toluene, methanol, ethanol, n-propanol, isopropanol, n-butanol or n-hexane; The second organic solvent is 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 11-mercaptoundecyltrimethoxysilane or silane-polyethylene glycol-mercapto; The fuel cell catalytic material contains a two-dimensional metal organic framework structure.
2. The method for preparing a fuel cell catalyst material according to claim 1, characterized in that: In step S01, the molar ratio of the metal salt to the organic ligand is 1:(1-3); the molar ratio of the metal salt to the activator is 1:(1-3); and the molar ratio of the metal salt to the reaction solvent is 1:(100-400).
3. The method for preparing a fuel cell catalyst material according to claim 1, characterized in that: In step S01, the metal salt is Al(NO3)3·9H2O, Cr(NO3)3·9H2O, Zn(NO3)2·9H2O or Zn(NO3)2·6H2O; The organic ligand is 2-aminoterephthalic acid, 5-aminophthalic acid, m-phenylenediamine or o-phenylenediamine; The active agent is one or a mixture of at least two of cetyltrimethylammonium bromide, tetramethylammonium hydroxide, disodium lauryl sulfosuccinate, disodium fatty alcohol polyoxyethylene ether (3) sulfosuccinate and sucrose ester; The reaction solvent is methanol, ethanol, ethylene glycol, propanol, propylene glycol, butanol, H2O, N,N-dimethylformamide or N,N-dimethylacetamide.
4. The method for preparing a fuel cell catalyst material according to claim 1, characterized in that: In step S02, the mass ratio of the powder to the first organic solvent is 1:(10-300); the mass ratio of the powder to the second organic solvent is 1:(1-10); and the mass ratio of the sulfur-functionalized powder to the oxidant is 1:(50-400).
5. The method for preparing a fuel cell catalyst material according to claim 1, characterized in that: In step S02, The oxidant is H2O2, KMnO4, HNO3, concentrated sulfuric acid, trivalent cobalt salt or potassium dichromate.
6. The method for preparing a fuel cell catalyst material according to claim 1, characterized in that: In step S02, the stirring time is 12h to 24h; The drying temperature is 30°C to 100°C.
7. The method for preparing a fuel cell catalyst material according to claim 1, characterized in that: In step S03, The mass ratio of the solid powder to the Nafion solution is 1: (1-18); the dispersion is achieved by stirring for 12h-96h.
8. The method for preparing a fuel cell catalyst material according to claim 7, characterized in that: In step S03, The mass ratio of the third organic solvent to the H2O is (2-5):1; The solid content of the catalyst is 2% to 10%; the I / C ratio of the catalyst is 0.5 to 1.
9. The method for preparing a fuel cell catalyst material according to claim 8, characterized in that: In step S03, The catalyst is a Pt / C catalyst; The third organic solvent is one or a mixture of at least two of n-propanol, isopropanol, methanol, ethanol and propanol; The ball milling time is 12h to 96h; The stirring time is 1h to 12h; The ultrasonic time is 0.3h~4h.
10. A fuel cell catalytic material, characterized in that: The fuel cell catalytic material is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of methanol fuel battery catalyst
CN109873172A
Sulfur-containing non-noble metal salt doped hollow nanometer metal organic framework material, and preparation method and application thereof
CN111138675A